Prevalence of blaOxacillinase-23 and blaOxacillinase-24/40 carbapenemase genes in Pseudomonas aeruginosa isolated from patients with nosocomial and non-nosocomial infections in West of Iran - Samaneh Rouhi; Rashid Ramazanzadeh (Iranian Society of Pathology, 2018)
Background and Objective: Pseudomonas aeruginosa (P. aeruginosa) causes serious nosocomial and non-nosocomial infections. blaOxacillinases (OXA)-23 and blaOXA24/40 provide resistance to carbapenem antibiotics. The aim of this study was assessment of blaOXA-23 and blaOXA-24/40 in P. aeruginosa isolated from patients with nosocomial and non-nosocomial infections. Methods: In this descriptive cross-sectional study performed in Sanandaj, Iran (Kurdistan province) in a period from December 2015 to August 2017, 146 isolates of Pseudomonas spp. were collected from patients' specimens. Microbiological methods and polymerase chain reaction (PCR) with gyrB were applied for P. aeruginosa detection. Disk diffusion method with imipenem (IMP) (10µg) was performed for detection of resistant bacteria, and multiplex PCR of OXA-23 and OXA-24/40 were performed as well. Stata 12 with Fisher's exact test and logistic regression were used for data analysis (P≤0.05).Results: PCR gyrB gene proved the existence of 91.78% P. aeruginosa isolates. Nosocomial infection with P. aeruginosa was observed in 41.79%. 27.61% of P. aeruginosa strains were resistant to IMP. blaOXA-23 and blaOXA24/40 were detected in 11.19% and 2.24% of the strains, respectively. 2.23% strains of P. aeruginosa showed a co-existence of blaOXA-23 and blaOXA24/40. There were no significant relationships between antibiotic resistance and presence of genes, and between IMP resistance and age, sex, city of residence, inpatient/outpatient, and specimen's type (P≥0.05).Conclusion: Resistance to IMP and the presence of resistant genes in this study were observed in patients. More precautions should be taken in prescribing antibiotics and applying molecular techniques to detect genes, since they can cause antibiotic resistant.